Arc in synaptic plasticity: from gene to behavior - Korb, Erica (2011)
The activity-regulated cytoskeletal (Arc) gene encodes a protein that is critical for memory consolidation. Arc is one of the most tightly regulated molecules known: neuronal activity controls Arc mRNA induction, trafficking, and accumulation, and Arc protein production, localization and stability. Arc regulates synaptic strength through multiple mechanisms and is involved in essentially every known form of synaptic plasticity. It also mediates memory formation and is implicated in multiple neurological diseases. In this review, we will discuss how Arc is regulated and used as a tool to study neuronal activity. We will also attempt to clarify how its molecular functions correspond to its requirement for various forms of plasticity, discuss Arc’s role in behavior and disease, and highlight critical unresolved questions.